2017
DOI: 10.1103/physrevb.96.014422
|View full text |Cite
|
Sign up to set email alerts
|

Variety of elastic anomalies in an orbital-active nearly itinerant cobalt vanadate spinel

Abstract: We perform ultrasound velocity measurements on a single crystal of nearly-metallic spinel Co1.21V1.79O4 which exhibits a ferrimagnetic phase transition at TC ∼ 165 K. The experiments reveal a variety of elastic anomalies in not only the paramagnetic phase above TC but also the ferrimagnetic phase below TC, which should be driven by the nearly-itinerant character of the orbitally-degenerate V 3d electrons. In the paramagnetic phase above TC , the elastic moduli exhibit elastic-mode-dependent unusual temperature… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…It is noted that, similar to NaCaCo 2 F 7 , the softening with minimum in C Γ (T ) is also observed in the frustrated spinel oxides, the origin of which is considered to be the coupling of the lattice to the spin-cluster excitations via the exchange striction mechanism [ 20,21,[23][24][25] ]. This spincluster-driven elastic softening is generally explained as the presence of a finite gap for the excitations, which is sensitive to strain [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noted that, similar to NaCaCo 2 F 7 , the softening with minimum in C Γ (T ) is also observed in the frustrated spinel oxides, the origin of which is considered to be the coupling of the lattice to the spin-cluster excitations via the exchange striction mechanism [ 20,21,[23][24][25] ]. This spincluster-driven elastic softening is generally explained as the presence of a finite gap for the excitations, which is sensitive to strain [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, as the ultrasound velocity can be measured with a high precision of ∼ppm, its measurements can sensitively probe elastic anomalies driven by phase transition, fluctuations, and excitations [ 18 ]. For the frustrated magnets, the ultrasound velocity measurements have proven to be a useful tool for studying not only the ground state but also the excited states [ [19][20][21][22][23][24][25][26] ]. In the present study on NaCaCo 2 F 7 , we find two different types of elastic anomalies at low temperatures above T f , which reveal, respec-tively, an isostructural lattice instability toward the spin freezing at T f and a trigonal lattice instability arising from the emergent dynamical spin-cluster state.…”
Section: Introductionmentioning
confidence: 99%
“…As the temperature further decreases, another magnetic transition from C-FM to noncollinear ferrimagnetic (NC-FM) occurs at T* ∼ 95 K, which is characterized by the spin reorientation. In addition, a second structural phase transition from I4 1 /amd to I4 1 /a occurs at ¢ T 1 ∼ 60 K. [11][12][13][14][15][16] This material is also known to exhibit spin canting, 17) and the saturation magnetization of the material is 1.5 μ B f.u −1 . 18,19) CVO has an extremely low electrical resistivity (ρ) of 0.065 Ωcm at RT; 20) therefore, it has been intensively investigated as a candidate electrode for secondary batteries.…”
Section: Introductionmentioning
confidence: 99%
“…The elastic modulus of a crystal is a thermodynamic tensor quantity, and the ultrasound velocity measurements of the symmetrically independent elastic moduli of a crystal thus provide symmetry-resolved thermodynamic information. In magnets, the modified sound dispersions caused by magnetoelastic coupling allow the extraction of detailed information on the interplay of the lattice and electronic degrees of freedom [ [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] ]. For LaCoO 3 , it has been reported that the longitudinal sound velocity along the cubic [111] direction has an unusual temperature dependence, which should arise from the spin crossover [ 48 ].…”
Section: Introductionmentioning
confidence: 99%